Phenotypic Screening and Genotypic Characterization of Extended- spectrum-beta-lactamase Producing Uropathogenic Escherichia coli (UPEC) isolated from a Tertiary Care Hospital in Bangladesh - Begum, Momtaz; Rahman, Tania; Sultana, Sharmeen; Saha, Shimu; SM Shamsuzzaman (Journal of Dhaka National Medical College & Hospital, 2023)
Beta-lactamases are the most important factors in the resistance to beta-lactam antibiotics among gram-negative bacteria, especially Escherichia coli. The prevalence of infections caused by extended-spectrum ß-lactamases (ESBLs)-producing Esch. coli is increasing, as one of the emerging health problems worldwide. This study aimed to investigate the prevalence of ESBL producing Esch. coli isolated from urinary tract infections (UTIs) and to observe the antibiotic resistance gene among them. Thiscross-sectional study was conducted in the Department of Microbiology, Dhaka Medical College from July 2015 to June 2016. Out of 280 urine samples with pus cells ≥5/HPF, 60 (72.29%) isolated bacteria was Escherechia coli identified by standard laboratory methods. Antibiotic susceptibility test was done by Kirby-Bauer disc diffusion method. ESBL producers were detected phenotypically by Double-disk-synergy (DDS) test. Genotypically ESBL genes (blaCTX-M-15 and blaOXA-1) among the ESBL producers were detected by PCR. Among 60 isolated Escherichia coli, 22 (36.67%) ESBL producers were detected by DDS test. Ten (45.45%) ESBL producers were positive for blaCTX-M-15, 5(22.73%) were positive for blaOXA-1 and 4(18.18%) isolates were harbouring the both ESBL genes. The results of this study showed high proportion of ESBL producing Esch. coli in Bangladesh. J. Dhaka National Med. Coll. Hos. 2023; 29 (02): 07-12